The mitochondria‐targeted hydrogen sulfide donor AP39 improves health and mitochondrial function in a C. elegans primary mitochondrial disease model. Issue 2 (20th January 2021) - Fox, Bridget C.; Slade, Luke; Torregrossa, Roberta; Pacitti, Dario; Szabo, Csaba; Etheridge, Timothy; Whiteman, Matthew
Abstract: Primary mitochondrial diseases (PMD) are inherited diseases that cause dysfunctional mitochondrial oxidative phosphorylation, leading to diverse multisystem diseases and substantially impaired quality of life. PMD treatment currently comprises symptom management, with an unmet need for therapies targeting the causative mitochondrial defects. Molecules which selective target mitochondria have been proposed as potential treatment options in PMD but have met with limited success. We have previously shown in animal models that mitochondrial dysfunction caused by the disease process could be prevented and/or reversed by selective targeting of the "gasotransmitter" hydrogen sulfide (H2 S) to mitochondria using a novel compound, AP39. Therefore, in this study we investigated whether AP39 could also restore mitochondrial function in PMD models where mitochondrial dysfunction was the cause of the disease pathology using C. elegans . We characterised several PMD mutant C. elegans strains for reduced survival, movement and impaired cellular bioenergetics and treated each with AP39. In animals with widespread electron transport chain deficiency ( gfm‐1[ok3372] ), AP39 (100 nM) restored ATP levels, but had no effect on survival or movement. However, in a complex I mutant ( nuo‐4[ok2533] ), a Leigh syndrome orthologue, AP39 significantly reversed the decline in ATP levels, preserved mitochondrial membrane potential and increased movement and survival. For the first time, this study provides proof‐of‐principle evidence suggesting that selective targeting of mitochondria with H2 S could represent a novel drug discovery approach to delay, prevent and possibly reverse mitochondrial decline in PMD and related disorders. Abstract :